Frequency of serological markers of rheumatoid arthritis in patients with Hashimoto’s thyroiditis - Ghozzi, Mariam; Mankai, Amani; Melayah, Sarra; Mechi, Fatma; Chedly, Zeineb; Trabelsi, Abdelhalim; Ghedira, Ibtissem (Laboratory medicine, 2024)
Abstract Background Hashimoto’s thyroiditis (HT) is an autoimmune disease that is frequently associated with other autoimmune conditions. Objective To perform serological screening for rheumatoid arthritis (RA) in patients with HT. Methods Our study included 88 consecutive serum specimens of patients with confirmed HT and 88 sex- and age-matched healthy subjects. All study participants were tested for anti-cyclic citrullinated peptides antibodies (CCP-Ab) and rheumatoid factor (RF). CCP-Ab and RF were performed using ELISA commercial kits. Statistical analysis was conducted using Epi Info, version 3. Results Out of 88 patients with HT, 15 (17.0%) had CCP-Ab or RF. The frequency of serological markers of RA was significantly higher in patients than in control individuals (17.0% vs 4.5%; P = .007). RF was more frequent in patients than in the control group, and the difference was statistically significant (13.6% vs 3.4%; P = .01). Isolated RF-IgM was absent in all controls and present in 6 patients with HT (6.8% vs 0%; P = .02). Out of 14 male patients, 3 (21.4%) had antibodies of RA. There was no significant difference in age between patients with CCP-Ab or RF and those without. Conclusion A high frequency of serological markers of RA was highlighted in patients with HT.